Do Characteristics of the Built Environment Influence Walking Behaviour Among Urban Adults? A Conceptual Framework, Systematic Review, and Research Plan - Thielman, Justin (Université d'Ottawa / University of Ottawa, 2014)
Objectives were to improve conceptualization of associations between built environment characteristics (BECs) and walking, synthesize evidence on associations, and propose future research that addresses limitations in existing studies. I designed a conceptual framework of hypothesized BEC - walking associations. I conducted a systematic review, searching MEDLINE, EMBASE, PsycINFO, and TRID for studies investigating BEC - walking associations. Two reviewers screened articles for inclusion. I assessed methodological quality and extracted data from included studies. I used the framework’s hypothesized associations to categorize and synthesize results, then analyzed study limitations and proposed future research that would address many limitations. The review identified 13 studies with 64 estimates that met all criteria. None of the framework’s hypothesized associations had a statistically significant majority of estimates that were statistically significant. Evidence is lacking on BEC – walking associations and more research is needed that addresses methodological issues such as heterogeneous BEC measures and geographic homogeneity.
Keywords: transportation; chronic disease; epidemiology; public health; health promotion; prevention; walkability; cities; housing; pedestrian; exercise; land use; sprawl